Basal lamina disorganisation of the acini and ducts of labial salivary glands from patients with Sjögren's syndrome: association with mononuclear cell infiltration. Issue 2 (13th July 2005) - Molina, C; Alliende, C; Aguilera, S; Kwon, Y-J; Leyton, L; Martínez, B; Leyton, C; Pérez, P; González, M-J
Abstract : Objective: To study the expression of laminin and type IV collagen as biomarkers of the organisation of the basal lamina of acini and ducts in labial salivary glands from patients with Sjögren's syndrome, and to relate this organisation to inflammatory cell invasion of acini and ducts. Methods: Immunohistochemistry for laminin and type IV collagen was undertaken on sections of labial salivary glands from 30 patients with Sjögren's syndrome, 10 control subjects, and 24 controls with chronic sialoadenitis. Immunohistochemistry reaction, alterations to cell morphology, and the presence of inflammatory cells in acini and ducts were evaluated and scored using a semiquantitative method. Results: Changes in the expression of laminin and type IV collagen in the basal lamina of acini and ducts of labial salivary glands from patients with Sjögren's syndrome were more pronounced than in labial salivary glands from control groups. A remarkable characteristic was the disorganisation of the basal lamina in the labial salivary glands in Sjögren's syndrome. The pattern of immunoreactivity of the basal lamina of other structures (for example, blood vessels) did not change. In Sjögren's syndrome, invasion of cytotoxic T lymphocytes was only observed in acini and ducts which had a disorganised basal lamina. Conclusions: The high state of disorganisation of the basal lamina of acini and ducts could allow invasion of cytotoxic T lymphocytes in Sjögren's syndrome, contributing to cell death and ductal hyperplasia.